ChemInform Abstract: Iron‐Catalyzed Arylmethylation of Sulfonyl Acrylamides. Issue 51 (5th December 2016) - Yu, Jin‐Tao; Hu, Weiming; Peng, Haibo; Cheng, Jiang
Abstract: An operationally simple arylmethylation/arylethylation of activated alkenes with tertiary alkyl peroxides as the alkyl source is developed which delivers α‐aryl‐β‐methyl amides in high yields.